Aspiration thrombectomy using a novel 088 catheter and specialized delivery catheter. (14th December 2021) - Caldwell, James; McGuinness, Ben; Lee, Shane S; Barber, P Alan; Holden, Andrew; Wu, Teddy; Krauss, Martin; Laing, Andrew; Collecutt, Wayne; Liebeskind, David S; Hetts, Steven W; Brew, Stefan
Abstract : Background: We describe the first-in-human experience using the Route 92 Medical Aspiration System to perform thrombectomy in the initial 45 consecutive stroke patients enrolled in the SUMMIT NZ trial. This aspiration system includes a specifically designed delivery catheter which enables delivery of 0.070 inch and 0.088 inch aspiration catheters. Methods: The SUMMIT NZ trial is a prospective, multicenter, single-arm study with core lab imaging adjudication. Patients presenting with acute ischemic stroke from large vessel occlusion are eligible to enrol. The study has had three phases which transitioned from use of the 0.070 inch to the 0.088 inch catheter. Results: Vessel occlusions were located in the internal carotid artery (27%), M1 (60%) and M2 (13%). Median baseline National Institutes of Health Stroke Scale (NIHSS) was 16 (IQR 10). Across the three phases, the first-pass reperfusion rate of modified Thrombolysis In Cerebral Infarction (mTICI) ≥2b was 62% using the Route 92 Medical system; this rate was 29% in phase 1, 56% in phase 2, and 80% in phase 3. The first-pass reperfusion rate of mTICI ≥2c was 42% overall, 29% in phase 1, 33% in phase 2, and 55% in phase 3. A final reperfusion rate of mTICI ≥2b was achieved in 96% of cases, with 36% of cases using adjunctive devices. Patients had an average improvement of 6.7 points in NIHSS from baseline at 24 hours, and at 90 days 48% were functionally independent (modified Rankin Scale 0–2). Conclusions: In this early experience, the Route 92 Medical Aspiration System has been effective and safe. The system has design features that improve catheter deliverability and have the potential to increase first-pass reperfusion rates in aspiration thrombectomy.